Phytochemical Analysis, Antioxidant, Antibacterial, Cytotoxic, and Enzyme Inhibitory Activities of Hedychium flavum Rhizome - Tian, Minyi; Wu, Xianghuan; Lu, Tingya; Zhao, Xiaoge; Wei, Feng; Deng, Guodong; Zhou, Ying (Frontiers in Pharmacology, 2020)
Hedychium flavum Roxb., a medicinal, edible, and ornamental plant, is widely cultivated throughout China, India, and Southeast Asia. The rhizome from this plant has been used for food flavoring and in traditional Chinese medicine to treat diverse diseases, but the detailed constituents and bioactivities are still limited known. Therefore, phytochemical analysis by GC-MS and UHPLC-Q-Orbitrap-MS, and antioxidant, antibacterial, cytotoxic, and enzyme inhibitory activities tests have been conducted in the current study. Based on the GC-MS results, the essential oil (EO) of rhizome was mainly composed of coronarin E (20.3%), β-pinene (16.8%), E-nerolidol (11.8%), and linalool (8.5%). Among them, coronarin E was reported in H. flavum EO firstly. Furthermore, the spectrophotometric indicated rhizome had high total phenolic content (TPC, 50.08–57.42 mg GAEs/g extract) and total flavonoid content (TFC, 12.45–21.83 mg REs/g extract), no matter in water extract (WE) or in 70 % ethanol extract (EE). UHPLC-Q-Orbitrap-MS was applied to further characterize composition, and 86 compounds were putatively identified from WE and EE, including 13 phenolic components. For the bioactivities, both WE and EE showed remarkable antioxidant activity by DPPH and ABTS tests, being superior to the positive control (butylated hydroxytoluene, BTH). EO revealed significant antibacterial activity against Staphylococcus aureus, Bacillus subtilis, Pseudomonas aeruginosa, and Proteus vulgaris with DIZ (10.34–24.43 mm), MIC (78.13–312.50 μg/mL), and MBC (156.25–625.00 μg/mL). Moreover, EO exhibited a considerable selectivity to human tumor cell K562 (IC50 = 27.16 μg/mL), and its toxicity was more than 3.5-fold different from that of non-cancerous MRC-5 cell (IC50 = 95.96 μg/mL) and L929 cell (IC50 = 129.91 μg/mL). A series of apoptosis analysis demonstrated that EO induced apoptosis against K562 cells in a dose-dependent manner. In enzyme inhibitory effect assays, WE and EE showed strong α-glucosidase inhibition activity, being superior to the positive control (acarbose). Besides, the EO, WE, and EE didn’t show a promising inhibition on tyrosinase (19.30–32.51 mg KAEs/g sample) and exhibited a weak inhibitory effect on cholinesterase. Based on the current results, H. flavum could be considered as a source of bioactive compounds and has high exploitation potential in the cosmetics, food, and pharmaceutical industries.